Evaluation of Food Habits, Physical Activity and Nutritional Status in Students 4 to 13 Years of Age in Llanquihue, Chile [Evaluación de Hábitos de Alimentación, Actividad Física y Estado Nutricional en Estudiantes de 4 a 13 Años de la Comuna de Llanquihue, Chile] - Flores-Calderon, C; Florez-Mendez, J (Sociedad Chilena de Nutricion Bromatologia y Toxilogica, 2020)
General data from the Junta Nacional de Auxilio Escolar y Becas (National School Grant and Scholarship Agency), indicate that the Los Lagos region ranks second in Chile for highest prevalence of overweight and obesity. The objective of this study was to evaluate eating habits and physical activity in Llanquihue, Los Lagos region. We evaluated eating habits and physical activity among 181 students between 4 and 13 years of age who were part of a larger sample (n= 1045) in which nutritional status was determined. Nutritional status was classified as normal, overweight, and obese, and was determined according to standards and regulations of the Ministry of Health. The results indicate that a majority of the students surveyed ate lunch at school, consumed foods high in refined sugar, packaged processed products, and junk food at least once a week. 58.6% of respondents did not engage in extra-programmatic physical activity. Finally, 29.4% of the total sample were overweight and 26.2% were obese. It can be concluded that eating and physical activity habits do not contribute to reversing the excess malnutrition figures detected in this study. © 2020, Sociedad Chilena de Nutricion Bromatologia y Toxilogica. All rights reserved.